Claiming a large slice of a small pie asymmetric disconfirmation in negotiation. [article]. - Larrick, Richard P.
Three studies how that negotiators consistently underestimate the size of the bargaining zone in distributive negotiations (the small-pie bias) and. by implication, overestimate the share of the surplus they claim (the large-slice bias). The authors explain the results by asymmetric disconfirmation: Negotiators with initial estimates of their counterpart's reservation price that are "inside" the bargaining zone tend to behave consistently with these estimates, which become self-fulfilling, whereas negotiators with initial "outside" estimates revise their perceptions in the face of strong disconfirming evidence. asymmetric disconfirmation can produce a population-level bias, even when initial perceptions are accurate on average. The authors suggest that asymmetric disconfirmation has implications for confirmations bias and self-fulfilling-prophecy research in social perceptions. -- (from the author)
Keywords: Confirmation bias; Learning from feedback; Negotiation; Self-fufilling prophecy; Triangle hypothesis